Routine Use of the "Penumbra" Thrombectomy Device in Myocardial Infarction: A Real-World Experience—ROPUST Study. (26th March 2022) - Tashtish, Nour; Chami, Tarek; Dong, Tony; Chami, Besher; Al-Kindi, Sadeer; Mously, Haytham; Janus, Scott; Hammad, Tarek; Shishehbor, Mehdi H.; Gupta, Anjan
Abstract : Objectives . Evaluation of the safety and efficacy of the Penumbra device as an adjunct to percutaneous coronary intervention (PCI) in patients with myocardial infarction (MI) and a large thrombus burden that requires thrombectomy. Background . For patients with acute MI, PCI is the primary reperfusion method. Large thrombus burden has always been a limitation of successful reperfusion. However, the use of current aspiration devices has been associated with an increased incidence of stroke. Methods . We performed a retrospective chart review at the University Hospitals Medical Center in Cleveland. Our study included data from patients who underwent PCI for ST segment elevation myocardial infarction (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI) assisted by the Penumbra Cat RX device (a wide-lumen thrombus aspiration catheter) between May 2019 and February 2021. The primary outcome was the final thrombolysis in myocardial infarction (TIMI) flow. The secondary endpoints were a composite of adverse cardiac events at 6 months. About 50% of the patients did undergo transfemoral PCI as per preference of individual operators. The Penumbra thrombectomy device can be used both by radial and femoral approach and does not need any different guide catheter use. Results . TIMI flow 3 was achieved in 111 patients (90.2%). The secondary endpoint occurred in 11 patients (8.9%, 3 MI, 8 heart failure hospitalizations). There were no stroke events or device-related complications. The door-to-balloon time was not affected by usage of the Penumbra device. Failure in the restoration of TIMI 3 flow was associated with the use of balloon angioplasty prior to the application of the Penumbra device, leading to distal embolization. Conclusions . The Penumbra Cat RX provides safe and effective thrombus removal with better clinical outcomes, even in high-risk patients with acute coronary syndrome.